A profibrotic role for thymic stromal lymphopoietin in systemic sclerosis. Issue 12 (14th February 2013) - Usategui, Alicia; Criado, Gabriel; Izquierdo, Elena; Del Rey, Manuel J; Carreira, Patricia E; Ortiz, Pablo; Leonard, Warren J; Pablos, José L
Abstract : Objetive: Systemic sclerosis (SSc) is an autoimmune disease characterised by progressive fibrosis. Although SSc shares pathogenetic features with other autoimmune diseases, the participation of profibrotic Th2 cytokines is unique to SSc, but the mechanisms of Th2 skewing are unknown. We have analysed the expression and function of thymic stromal lymphopoietin (TSLP), a central regulator of Th2-mediated allergic inflammation, in human SSc, primary lung fibrosis and in a mouse model of scleroderma. Methods: TSLP expression was analysed by immunohistochemistry in human SSc skin, primary lung fibrosis and mouse bleomycin-induced skin fibrosis, and by quantitative RT-PCR in mouse skin and cultured fibroblasts. The regulation of TSLP expression by specific toll-like receptors (TLR)-2, -3 and -4 agonists was analysed in human dermal fibroblast cultures. The role of TSLP in skin fibrosis and local cytokine expression was analysed in TSLP receptor (TSLPR)-deficient mice. Results: TSLP was overexpressed by epithelial cells, mast cells and fibroblasts in human SSc skin and lung fibrosis, and in the bleomycin model of scleroderma. In cultured human and mouse skin fibroblasts, TSLP expression was inducible by activation of TLR, particularly TLR3. In TSLPR-deficient mice, bleomycin-induced fibrosis was significantly reduced in parallel with significantly reduced local expression of IL-13. Conclusions: These data provide the first evidence of TSLP overexpression in SSc and other non-allergic fibrotic conditions, and demonstrate a profibrotic role that is potentially meditated by specific changes in the local cytokine milieu. Thus, modulating TSLP may have antifibrotic therapeutic implications.